The Brazilian connection in Milton Friedman's 1967 presidential address and 1976 Nobel lecture - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2018)
The paper investigates the role played by Friedman's interpretation of the Brazilian inflation in his 1967 formulation of the natural rate hypothesis and in his 1976 discussion of indexation and other institutional arrangements in the face of chronic inflation. It is argued that, as an empirical economist and in the absence of evidence from industrialized countries, Friedman found in the Brazilian 1964-66 stabilization episode significant support for his argument about inflation acceleration and a shifting Phillips curve. Friedman's interest in the Brazilian inflationary economy prompted him to visit the country in 1973. The context and implications of Friedman's Brazilian travel are also tackled in the paper.
Keywords: B22; B31; E31; 330; Friedman; Brazil; inflation; Phillips curve; expectations